Yusuf Hussain’s Role in Critical Interpretations of Urdu Ghazal: اردو غزل کی تنقیدی تعبیرات میں یوسف حسین کا کردار (DARYAFT, 2023)
Yusuf Hussain was proficient in different languages. His criticism also holds a prestigious position in Urdu literature. His book "Urdu Ghazal" is regarded as a complete addition to Urdu criticism. In this book, he has thoroughly reviewed all aspects of Urdu Ghazal along with a complete analysis. Although the basic reality of ghazal has not been affected much, there have been equal changes in the style of Urdu ghazal. He is a supporter of classicism in ghazal and in his opinion, the main motivational elements of ghazal are passion and imagination, due to which the heart is filled with joy and excitement. Like other critics and poets, he is also convinced of love in Urdu ghazal. It has been solved in a critical manner. In his opinion, creation is not possible without grief, so the colour of Sufism is also dominant in Urdu Ghazal. His special thing is that he has presented his arguments and critical ideas in an effective manner without finding flaws in the criticism of others, that is why he is known as a reliable critic.